Respuesta :
Answer:
x=1
Step-by-step explanation:
First we need to simplify and factorize the denominator as shown below:
[tex]f(x)=\frac{9(x-6)}{x^{2} -7x+6} \\\\ f(x)=\frac{9(x-6)}{x^{2}-6x-x+6 }\\\\ f(x)=\frac{9(x-6)}{x(x-6)-1(x-6)}\\\\ f(x)=\frac{9(x-6)}{(x-1)(x-6)}\\[/tex]
Following points must be kept in mind:
- A hole exists at the value at which both numerator and denominator of the rational function becomes zero
- Vertical asymptote exist where only the denominator is zero.
For x=6, both numerator and denominator are zero so we have a hole here. At x=1, only the denominator is zero, so we have a vertical asymptote here.
Thus the vertical asymptote of f(x) is at x=1
Answer:
[tex]x=1[/tex]
Step-by-step explanation:
For the function [tex]f(x)=\frac{9(x-6)}{x^2-7x+6}[/tex], you need to factor the denominator.
Find two number that when you add them you get -7 and when you multiply them you get 6. These numbers are -6 and -1.
Then:
[tex]f(x)=\frac{9(x-6)}{(x-6)(x-1)}[/tex]
Simplify:
[tex]f(x)=\frac{9}{(x-1)}[/tex]
Observe that the denominator is equal to zero in [tex]x=1[/tex].
Therefore, when x approaches 1, f(x) tends to infinite.
Then the vertical asymptote s:
[tex]x=1[/tex]